Out of sight is out of mind? Experimentally testing a gradually materializing public bad - Alexander Egberts; Christoph Engel; Joshua A. T. Fairfield (Max Planck Institute for Research on Collective Goods, 2024)
Many social ills can be modelled as a public bad. In such scenarios, private benefit is often immediate while the public damage takes some time to materialize. In this experiment, we investigate the behavioral effects caused by such delays in the realization of collective harm. By manipulating the weight with which the damages caused by group contributions are carried over to the next round, we alter the number of periods required for the social damage to fully unfold. We keep constant the economic consequences of contributions between treatments (by introducing a multiplier for the damage) and between periods (by deducting all unrealized harm at the end of the game) to avoid multiple equilibria. In a second treatment dimension, we isolate the cognitive challenges of this experiment by replacing human group-members with "computerized players" which perfectly copy each subject's previous behavior. We find that participants' behavior is less cooperative over time when harm is deferred into the future. Our results also suggest that the driving mechanism behind this effect is not insufficient anticipation, but the lack of having experienced the negative consequences of the public damage.
hdl:21.11116/0000-0010-3CA2-4
Keywords: C91; D62; D91; H41; K24; K32; 330; public bad; dynamically developing social harm; cognitive and motivational challenge; experiment